Electrically induced patterns in nematics and how to avoid them. Issue 2 (2nd July 2016) - Éber, N.; Salamon, P.; Buka, Á.
ABSTRACT: Electric field-induced patterns in liquid crystals have been observed and studied for about 50 years. During this time, a great variety of structures, detected under different conditions, have been described; theoretical descriptions were also developed parallel with the experiments and a huge number of papers have been published. The non-vanishing interest in the topic is due to several factors. First, most experimentalists working with new (or even well-known) liquid crystals apply sooner or later an electric field for different purposes and, as a response, often (maybe undesirably or unexpectedly) have to face with emergence of patterns. Second, understanding the complexity of the formation mechanism of regular patterns in a viscous, anisotropic fluid is an extremely challenging theoretical task. Third, specialists in display fabrication or in other applications are also interested in the results; either to make use of them or in order to avoid field-induced patterns. In this review, we attempt to provide a systematic overview of the large amount of published results, focusing on recent achievements, about the three main types of electric field-induced patterns: transient patterns during the Freedericksz transition, flexoelectric domains and electroconvection. As a result of different instability mechanisms, a variety of pattern morphologies may arise. We address the physical background of the mechanisms, specify the conditions under which they may become effective, discuss the characteristics of the patterns, and summarize the possibilities of morphological transitions induced by frequency, voltage or temperature variations. Special emphasis is given to certain topics, which recently have gained enhanced interest from experimental as well as theoretical point of view, like driving with ultra-low frequencies or non-sinusoidal (superposed) waveforms, and the dynamics of defects and embedded colloidal particles. Assisting newcomers to the field, we also mention some, yet unresolved, problems, which may need further experimental and/or theoretical studies.